The impact of reflective practices on student learning in remote internships during COVID 19 pandemic: a qualitative study. Issue 4 (4th July 2022) - Bhuwandeep,
ABSTRACT: Reflective practice, in simplest form, means recalling about one's experience to learn from it and plan future course of action. Reflective practice is quite popular in educational field to impart deeper insights to the students. However, there is a scarce understanding of how students reflect during online internships (on their own), outside the realms of traditional classroom. Hence, this paper endeavors to study how students reflect during internships and subsequent impact of reflective practices on students' learning during internship. The study was conducted on nine voluntary students who participated in reflective practices during their eight-week internships. Their experiences, post internships, were analyzed (using thematic analysis). The analysis generated three themes for reflection among students. They are hypothesis testing during uncertainty, metacognition, and future planning based on the lessons learned. The empirical study also uncovers how reflective practice leads to self-awareness, self-regulation, and professional grooming, stress relief during internship. The managerial implication for educational institutes is to include faculty guided and group led reflective assignments in curriculums for better experiential learning. Our study contributes to growing literature of reflective practices in educational field outside the conventional classroom setting.